Can ethnic background differences in children's body composition be explained by differences in energy balance-related behaviors? A mediation analysis within the energy-project. - Juan Miguel Fernández-Alvira (Public Library of Science (PLoS), 2013)
Background In affluent countries, children from non-native ethnicity have in general less favourable body composition indicators and energy balance-related behaviors (EBRBs) than children from native ethnicity. However, differences between countries have been reported. Methodology/principal findings A school-based survey among 10-12 years old children was conducted in seven European countries with a standardized protocol. Weight, height and waist circumference were measured; engagement in EBRBs was self-reported. For those countries with significant ethnic differences in body composition (Greece and the Netherlands), multilevel mediation analyses were conducted, to test the mediating effect of the EBRBs in the association between ethnic background and body composition indicators. Analyses were adjusted for gender and age, and for parental education in a later step. Partial mediation was found for sugared drinks intake and sleep duration in the Greek sample, and breakfast in the Dutch sample. A suppression effect was found for engagement in sports activites in the Greek sample. Conclusions/significance Ethnic differences in children's body composition were partially mediated by differences in breakfast skipping in the Netherlands and sugared drinks intake, sports participation and sleep duration in Greece.